Potensi Nasi Aking Sebagai Piring Biodegradable (Bioplastik) Ditinjau Dari Karakteristiknya - Hamidah Hamidah; Hasan Muzaki; Nurul Kholidah (Stannum : Jurnal Sains dan Terapan Kimia, 2021)
Rice flour is biopolymer that be used the main ingredient for making bioplastic (Biodegradable plate). Product formation is done rice flour dan startfruit (Averrhoa bilimbi L). The purpose of this study was to determine the effect of adding starfruit filtrate (Averrhoa bilimbi L) to water absorption and biodegradation. This study uses the phase inversion method with variations in the volume of the startfruit filtrate (Averrhoa bilimbi L) much as 10 ml,15 ml, 20 ml, and 25 ml. The result of the formation of biodegradable plates with the addition of startfruit (Averrhoa bilimbi L) filtrate produce a brown color, hard texture, and rough on the surface og the product. The Result showed that each addition of starfruit filtrate (Averrhoa bilimbi L) volume could increase the charachteristic of water absorption and biodegradation with each percentage 48,29 %, 51,78 %, 53,62%, 55,27 % and 11,77 % 24,52 %, 28,42 %, 36,88 %. Confirmation of the product surface through scanning electron microscopy provides information that the resulting bioplastic has a less dense particle arrangement and the formation of pores on the surface. starfruit filtrate (Averrhoa bilimbi L) can be used in modifying because contains compounds that are weakly acidic with pH 5.